Building Regulation for Resilience : Managing Risks for Safer Cities - World Bank Group (World Bank, Washington, DC, 2016)
The global toll of human suffering and material loss due to disasters has led to growing public concern and expanded institutional response in the form of disaster relief and recovery assistance from individuals, governments, and intergovernmental organizations. Initial humanitarian concern has primarily been focused on dealing with the consequences of disasters. However, we must begin to address the causes of these events while ensuring the implementation of policies to reduce disaster risks or losses. Low- and middle-income countries will experience a doubling of their building stocks in the next 15- 20 years, and it is crucial to assure that this new construction does not recreate and expand the disaster vulnerability of the present. Priority must be placed on the production of safe and resilient cities, communities, and homes. While safer, code-compliant construction may add to initial construction costs, these investments can be balanced against the reduced loss of life and property in future disasters. The agenda provides the international community with an opportunity to leverage regulatory governance as a powerful means to shift the focus from post-disaster relief and response to proactive population protection, disaster prevention, and sustainable and resilient urban development.